Timeline: History of the Electric Car, Trends and the Future Developments - P.R.Fayziyev; I.A.Ikromov; A.A.Abduraximov; Q.M.Dehqonov (Genius Journals, 2022)
Today, the sale of electric cars in the world car market is growing rapidly. It is no secret that the world's largest car brands are replacing a significant part of their cars with electric cars. The main reason for this is the use of environmentally friendly fuels (electricity) as fuel for the car, which is one of the most renewable on the planet. It is no secret that the use of electricity for cars today is the biggest step taken to restore our polluted planet.
Keywords: Hybrid car; electric car; Immissionschutzgesetz Luft; green cars